(untitled) (Jurnal Hortikultura Indonesia, 2023)
A technology of shallots cultivation in general is already widely known and practiced. However, in particular the local shallots of the Lembah Palu variety (Allium cepa L.) Aggregatum group) are not widely known to the wider community. This shallot type is used as an industrial raw material for prime quality fried shallots. The aimed of this article review was to carry out technological studies in order to increase the productivity of shallots of the Lembah Palu variety (SLPV). In this review article, various components of SLPV cultivation technology were outlined, including aspects of the growing environment, handling of tubers and seeds, planting patterns and plant spacing, fertilization and plant response, plant growth regulators (PGR), irrigation water management, pest and disease control, and modification of the microenvironment. Some of the results of this technology study have been used by researchers, academics, and farmers as a reference for increasing SLPV productivity, especially in production centers in the Lembah Palu Valley area, Central Sulawesi. Keywords: bulbs, fertilization, fried onions, superior, vegetables